Investigation of the effect of aggregate obtained from Çatakören region in Bolu on the crucial properties of conventional concretes - Bahattin Öztoprak (Journal of New Results in Science)
This current study delved into the not only meticulous characterization of the aggregate obtained from Çatakören region in Bolu but also its usage potential in the production of traditional concretes. The compressive strength, slump grade, apparent density of the three types of prepared concretes (C25/30, C30/37 and C35/45) as well as microstructural properties of the fractured samples via SEM were investigated in details. Furthermore, all the characteristic properties of the component such as cement, set accelerating admixture, water reducing admixture and the aggregates were determined with the aid of analyses carried out according to the relevant standards. As for the aggregate, the physical, qualitative mineralogical, petro-graphic, X-ray diffraction, mechanical besides the grain size distribution limits properties of the aggregates investigated successfully. In the light of these analyses, it was found that the aggregates produced from Çatakören region was considerable proper and had more usability potential for the production of the traditional concretes meeting the standards. Additionally, among the produced concrete samples, the maximum compressive strength value, 51.3 MPa were obtained from C35/45 concrete samples as expected due to the usage of the relatively larger amount of cement and admixture in the production of this concrete. SEM analyses also showed that the formation of better interfacial adhesion and more stronger chemical bonds, especially in C-S-H were formed in the concrete matrix due to the probable decrement in the porosity. Furthermore, it was apparent from the images that there existed voids, space, ettrengites , microcracks besides the structures regarding as C-H and C-S-H in the concrete matrix.